Jeff Freeman interviewed by Rob Willis in the Rob and Olya Willis folklore collection - Freeman, Jeff, 1951-; Willis, Rob, 1944- (2009)
Folkloric recording. Jeff Freeman talks about his early days and trade as a saddler; blacksmithing; making buckles, brands and spurs; his fascination for bushranger history; his own research and thoughts into Ben Hall and other bushrangers.
Recorded by John Harpley.
Summary accompanied by photographs.
Recorded on 16 September 2009 at Eugowra, N.S.W.
Mode of access: Online.
Jeff Freeman is the great, great, grandson of bushranger, John McGuire who was involved in the Gold Escort robbery at Eugowra, N.S.W.
Timed summary (3 p.)
Keywords: Freeman, Jeff, -- 1951- -- Interviews; Hall, Ben, -- 1837-1865 -- Anecdotes; Bushrangers -- New South Wales -- Eugowra Region; Bushrangers -- New South Wales -- History; Robbery -- New South Wales -- Eugowra Region; Eugowra Region (N.S.W.) -- History; Saddlers